Fractal Enterprise Model in Intangible Resource Analysis: Double-Hierarchy Method - Klyukina, Victoria (Complex systems informatics and modeling quarterly, 2025)
In global competition, tangible resources as a differentiating factor of competitive advantage are losing their power. The subject of intangibles and knowledge management is associated with high economic performance and, thereby, becomes increasingly significant in strategy implementation. This article explores how Enterprise Modeling (EM) can be used to mitigate the gap between the theoretical stands on the importance of the intangibles and their practical application. In particular, the study presents the application of the Fractal Enterprise Model (FEM) in strategic resource analysis. This research aims to propose a double-hierarchy resource modeling method using FEM and the patterns developed using this method. Additionally, this article presents an example of the method’s application in a real case. The business situation concerns the structural change within the product development processes in pursuit of strategic leadership. The study deploys the Design Science Research (DSR) methodology and generates new knowledge about EM application in intangible resource management.